2018
DOI: 10.1063/1.5023422
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of inversion-domain boundaries in aluminum nitride: Interplay between interface energy and electric dipole potential energy

Abstract: Aluminum nitride (AlN) has a polar crystal structure that is susceptible to electric dipolar interactions. The inversion domains in AlN, similar to those in GaN and other wurtzite-structure materials, decrease the energy associated with the electric dipolar interactions at the expense of inversion-domain boundaries, whose interface energy has not been quantified. We study the atomic structures of six different inversion-domain boundaries in AlN, and compare their interface energies from density functional theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…2, there are sparse {1010} planes, conventionally called type 1, and dense {1010} planes, called type 2. Our calculations and previous works [29,30] indicate that for all studied cases of {1010} planar defects the type 1 defects are energetically favorable compared to the type 2 defects. Thus, in the rest of this document, unless explicitly stated otherwise any {1010} planar defect we discuss or illustrate will be of type 1.…”
Section: A Inversion Domain Boundariessupporting
confidence: 76%
“…2, there are sparse {1010} planes, conventionally called type 1, and dense {1010} planes, called type 2. Our calculations and previous works [29,30] indicate that for all studied cases of {1010} planar defects the type 1 defects are energetically favorable compared to the type 2 defects. Thus, in the rest of this document, unless explicitly stated otherwise any {1010} planar defect we discuss or illustrate will be of type 1.…”
Section: A Inversion Domain Boundariessupporting
confidence: 76%
“…The IDB model is constructed from the two grains with different polarized directions and has irregular distorted bonding structures unlike bulk wurtzite phase (Figure S1). 27,28 To confirm the reliability of the designed IDB models, the thermodynamic stability of IDB structures was examined by AIMD at 300 and 600 K. Figure S2 represents stabilized atomic structures of AlN, AScN, and GaN models at 300 and 600 K. The IDB models of all materials maintain the atomic arrangements of the IDBs at the grain boundary comparable to IDB models stabilized by DFT for both temperatures. Consequently, the IDB models are considered thermodynamically stable and structurally reliable.…”
Section: Resultsmentioning
confidence: 97%
“…24−26 The polycrystal-line wurtzite nitride growth results in the formation of both metal (e.g., Al, Ga, and Sc) polar and N polar grains that generate inversion domain boundaries (IDBs) between the grains of different polarities. 27 The IDBs were examined structurally to find reliable atomic arrangements. 28 However, the comprehensive characteristics of IDBs of these wurtzite nitrides have not been modeled even though the polycrystalline phase with IBDs is known to deteriorate the material properties (e.g., thermal, optical, and piezoelectric properties).…”
Section: Introductionmentioning
confidence: 99%
“…Recently reported thermodynamics based first principle calculation of IDs showed that their interface energies are highly correlated with the structural distortions of bond lengths and bond angles. 108 Surface preparation and etching.-The preparation of nearlyatomically flat surface and the determination of the etching properties of AlN substrates as well is of great importance for their further usage in epitaxial growth and device preparation. Different polishing procedures were developed by various research groups based on mechanical and chemical-mechanical (CMP) processes.…”
Section: Status Of Bulk Aln Crystal Growthmentioning
confidence: 99%